Analisis Pengaruh Zakat terhadap Kinerja Keuangan: Studi Literatur - Agus Munandar; Dade Nurdiniah; Donant Alananto Iskandar (LPMP Imperium, 2019)
This paper aims to investigate the effect of zakat payment towards financial performance. It is important because some previous researchs show inconclussive result regarding the impat of zakat payment on financial performace of companies. Based on theory of signalling, zakat is corporate charity activity which produces good news and enhances corporate reputation, in turn, increase corporate financial performance. Based on some literatures and theory, this study provides an argument that zakat has positive impact on corporate financial performance. This study has impact on future research that zakat is important variable for financial performance study. Also, this paper provides insight into the nature of zakat payment and financial performance measurement.